The Transaction-Cost Roots of Market Failure - Tamara Todorova (Journal of Advanced Research in Management, 2015)
Our purpose is to reveal the transaction cost character of the different forms of market failure where transaction costs are defined as the costs of using the market mechanism, what it costs to organize market exchange or overcome the obstacles to an efficient market process. The paper thus inevitably attempts at defining market failure in this new context. It also studies market power, externalities, opportunism and informational asymmetries as the different forms of market failure from the perspective of transaction cost theory. We discuss public goods and the role of the state in overcoming the marketing costs of private transacting. This role would be stronger in economic systems faced with sizable transaction costs and thus more prone to market failure where market failure becomes a true obstacle for economic development.
Keywords: I31; O11; P0; 330; transaction costs; market failure; economic development